The social orientations and ideologies of UK finance employees at the onset of the Global Financial Crisis. (June 2017) - Cebulla, Andreas
Debates about the Global Financial Crisis of 2007 have pointed at institutional and individual-behavioural factors as its causes. Using the British Household Panel Survey, this article highlights marked differences in perceptions of societal and economic fairness among financial services employees in investment or management positions in the United Kingdom and the general working population at the brink of the Global Financial Crisis. Panel data analysis suggests that financial services and occupations did not necessarily attract employees with pro-market attitudes, but that employment in these institutions and occupations made it more likely that employees came to display these perceptions, contributing to the construction of a distinct attitudinal profile of finance employees.